Synthesis of acrolein by gas-phase dehydration of glycerol over silica supported bronsted acidic ionic liquid catalysts - Munshi, Mudassir K.; Lomate, Samadhan T.; Deshpande, Raj Madhukar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Chemical Technology and Biotechnology, 2010)
BACKGROUND: Glycerol has become readily available as a byproduct from the biodiesel industry. High functionality and relatively low price make it a potential building block to produce value-added derivatives such as acrolein. RESULTS: Dehydration of glycerol to acrolein was performed over several silica supported Bronsted acidic ionic liquids as catalysts. All the catalysts prepared were active for the synthesis of acrolein (conversion of glycerol was observed in the range 35-90% with selectivity to acrolein in the range 29-58%). CONCLUSIONS: Catalyst prepared from triphenyl (3-sulfopropyl) phosphonium 4-methylbenzenesulfonate gave good activity and selectivity at 4 h reaction time. The conversion of glycerol decreased with increase in glycerol concentration. Higher temperature (325 degrees C) resulted in significantly lower conversion as well as selectivity to acrolein. With the use of two additional traps cooled to -7 degrees C, the selectivity to acrolein increased significantly for good catalysts. (C) 2010 Society of Chemical Industry
Keywords: acidic ionic liquids; acrolein; glycerol dehydration; supported catalyst

Catalytic dehydration of lactic acid to acrylic acid using calcium hydroxyapatite catalysts - Ghantani, Vidhya C.; Lomate, Samadhan T.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Green Chemistry, 2013)
A series of calcium hydroxyapatite (HAP) catalysts were synthesised with a Ca/P ratio ranging from 1.3 to 1.89 by a co-precipitation method that involved changing the pH of the calcium and phosphorous precursors. The physicochemical characterization by XRD, SEM, BET surface area and CO2 and NH3-TPD techniques confirmed the hydroxyapatite formation. These HAP catalysts were used for the vapour phase dehydration of lactic acid to acrylic acid. The HAP catalyst with a Ca/P ratio of 1.3 was found to be the most efficient catalyst among the synthesised series, which gave 100% conversion of lactic acid and 60% selectivity towards acrylic acid at 375 degrees C when a 50% (w/w) aqueous solution of lactic acid was used. The higher selectivity towards acrylic acid has been correlated to the increased acidity and reduced basicity of the HAP catalyst with a Ca/P ratio of 1.3 compared to the other HAP catalysts. The catalyst was found to be very stable and no deactivation was observed even after 300 h of reaction time. In situ FTIR studies were performed for understanding the mechanistic aspects and showed the formation of calcium lactate as an intermediate species during the dehydration of lactic acid to acrylic acid.